Les tourbières réticulées du Québec-Labrador subarctique : interprétation morphoclimatique - Hamelin, Louis-Edmond (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1957)
In order to indicate the trend of his research, the author first reviews sortie books and articles that deal with similar problems. Then he carefully describes the string-bogs which are essentially a marshy zone formed of ponds separated by strips of vegetation. String-bogs present a rectilinear or a concentric pattern. Their characteristics make them different from other types of peat bogs.String-bogs are found in the Québec-Labrador peninsula inside a zone of which the Southern limit is the 50 th parallel and the Northern limit is approximately the 55 th parallel. The author's objective is to determine the morphoclimatic significance of that phenomenon. This type of string-bogs is usually found in areas of poor drainage ; it is also related to an optimum thickness of peat ; we find it jar South of the perma-frost limit in a region where snow maintains a great depth. It is a recent phenomenon though not necessarily contemporary; it dates from the cold period immediately preceding the present geological age. In order to explain the formation of string-bogs, the author envisions a combination of processes in which either one or the other can dominate locally. The processes are sub-aquatic solifluction, the gathering of isolated vegetation covered hillocks, the tearing of the plant covering by internal balls of ice, the shifting of a material as malleable as peat, the differential formation of ice in the ponds and the action of snow. These string-bogs do not form a part of « normal » geomorphology.